EFFECT OF MANAGEMENT STRUCTURES ON ACCOUNTS RECEIVABLES MANAGEMENT IN THE HOTEL INDUSTRY IN KENYA - Ngugi, Simon K.; Gakure, Prof. Roselyn W.; Gekara, Dr. Geoffrey M; kahiri, Dr. James K. (American Journal of Accounting, 2017)
Purpose: The purpose of the study was to determine the effects of management structures on accounts receivables management in the hotel industry in Kenya Methodology: The target population of the study was 47 hotels and lodges in Kenya. A sample of 141 respondents was selected using stratified random sampling in each hotel and lodge to group respondents into three strata. The strata were that of top management, finance staff and credit control staff. This study used both primary and secondary data. Data collection methods used included: questionnaires and secondary data collection guide. Secondary data was collected for all variables for a period of three years (2007 to 2010).. Information was sorted, coded and input into the statistical package for social sciences (SPSS) for production of graphs, tables, descriptive statistics and inferential statistics. In particular, means, standard deviations, and frequencies. Inferential statistics such as factor analysis and odd ratio regression were also used. Results: Based on the findings, the study concluded that management structures had an effect on accounts receivables management at the hotel industry in Kenya. It can therefore be concluded that there was an effective system for managing accounts payable and receivable and a monthly operating budget in hotels and the management was concerned with providing additional information to improve the clarity and comprehensiveness of the company's accounts receivables. Unique contribution to theory, practice and policy:Based on the findings, the study recommends that the hotel management should ensure the staff offers high quality services so as to attract and retain their customers.